High-fidelity 2-way FSI simulation of a wind turbine using fully structured multiblock meshes in openfoam for accurate aero-elastic analysis - Zhangaskanov, Dinmukhamed (2023)
With increased interest in renewable energy, the power capacity of wind turbines is constantly increasing, which leads to increased rotor sizes. With ever larger rotor diameters, the complex and non-linear fluid-structure interaction (FSI) effects on wind turbine aerodynamic performances become significant, which can be fully studied using hi-fidelity 2-way FSI simulation. In this study, a two-way FSI model is developed and implemented in Openfoam to investigate the FSI effects on the NREL Phase VI wind turbine. The fully structured multiblock (MB) mesh method is used for the fluid and solid domains to achieve good accuracy. A coupling method based on the ALE is developed to ensure rotation and deformation can happen simultaneously and smoothly. The simulation results show that hi-fidelity CFD (Computational Fluid Dynamics) and CSD (Computational Structural Dynamics) -based 2-way FSI simulation provides high accurate results for wind turbine simulation and multi-disciplinary design optimization (MDO).